Mapping the potential distribution of plants and animals for wildlife management: the use of the DOMAIN software package - Gillison, A.N. (1997)
An adequate knowledge of species distribution and performance is fundamental to effective wildlife management. In the majority of cases where known distributions are very limited, other means of acquiring information may be needed to model the potential distribution of species of management concern. This paper briefly reviews some available software packages including the recent ‘Windows’ version of DOMAIN developed at CIFOR. Unlike some other potential mapping packages, the DOMAIN program can work efficiently with relatively few known distribution points. These are correlated with the values of other spatially referenced, environmental variables such as elevation, soils, vegetation type and climate that are considered to influence species distribution. A habitat envelope or environmental domain is then computed based on these correlates. The algorithm then matches the template with the known environmental values for all pixels in the area under study and maps out similarity classes. In this way a rapid appraisal of the potential distribution of one or more species can be made for any area where there are available relevant, spatially referenced environmental data. A case study from Central Sumatra demonstrates how the method may be used to generate maps of plant species diversity or richness.